2006
DOI: 10.1098/rsta.2006.1786
|View full text |Cite
|
Sign up to set email alerts
|

Modelling aspects of cancer dynamics: a review

Abstract: Cancer is a complex disease in which a variety of factors interact over a wide range of spatial and temporal scales with huge datasets relating to the different scales available. However, these data do not always reveal the mechanisms underpinning the observed phenomena. In this paper, we explain why mathematics is a powerful tool for interpreting such data by presenting case studies that illustrate the types of insight that realistic theoretical models of solid tumour growth may yield. These range from discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
163
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(178 citation statements)
references
References 45 publications
1
163
0
7
Order By: Relevance
“…Given an initialized level set function ϕ, only the points that fall within a fixed distance of the interface are updated during level set operations (e.g., velocity extensions and level set reinitialization). In the level set context, the narrow band can be identified by (9) where R > 0 is a fixed constant that is chosen to suit the problem. In our work with the tumor problem, we use R = 20Δx.…”
Section: Narrow Band/local Level Set Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Given an initialized level set function ϕ, only the points that fall within a fixed distance of the interface are updated during level set operations (e.g., velocity extensions and level set reinitialization). In the level set context, the narrow band can be identified by (9) where R > 0 is a fixed constant that is chosen to suit the problem. In our work with the tumor problem, we use R = 20Δx.…”
Section: Narrow Band/local Level Set Methodsmentioning
confidence: 99%
“…Cancer is a fundamental scientific and societal problem, and in the past several decades, intensive research has been focused on understanding the complexity of cancer progression, developing new therapies, and formulating optimal treatment protocols. While much work has been done in the mathematical community on tumor modeling (e.g., see the reviews [3,6,7,9,46,47]), to date there has been little work in modeling tumor growth in realistic, heterogeneous tissues on large spatial scales. The methods we present in this paper will provide the foundation for a biologically-detailed millimeter-to-centimeter-scale model of tumor growth in heterogeneous tissues with realistic features (e.g., mechanically soft and hard regions, bone, and inhomogeneous nutrient delivery) [33,35,39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study we introduce angiostatin locally in the 4th month of tumor development and continue its administration till the end of month 10. This inhibitor neutralizes the growth factor directly as described by (2). We apply AST off-center in the lower left quadrant and not inside the tumor, to prevent the vessels from reaching the tumor at all.…”
Section: Growth Inhibition Through Angiostatinmentioning
confidence: 99%
“…Simulation of such complex systems are computationally most demanding, yet the rapid development of hardware, especially emerging distributed parallel computing concepts, enable more and more realistic modeling of physiological systems. Tumor development has been studied extensively over the last three decades, reviews and exhaustive survey of the approaches can be found elsewhere [1,2] or more recently in [3]. A further discussion of the relevant literature may be found in our previous works [4,5].…”
Section: Introductionmentioning
confidence: 99%